How Abstract (Non-embodied) Linguistic Representations Augment Cognitive Control - Kompa, Nikola A.; Mueller, Jutta L. (Frontiers in Psychology, 2020)
Recent scholarship emphasizes the scaffolding role of language for cognition. Language, it is claimed, is a cognition-enhancing niche (Clark, 2006), a programming tool for cognition (Lupyan and Bergen, 2016), even a neuroenhancement (Dove, 2019), and augments cognitive functions such as memory, categorization, cognitive control as well as meta-cognitive abilities (‘thinking about thinking’). Yet the notion that language enhances or augments cognition does not fit in with embodied approaches to language processing, or so we will argue. Accounts aiming to explain how language enhances various cognitive functions often employ a notion of abstract representation. Yet embodied approaches to language processing have it that language processing crucially, according to some accounts even exclusively, involves embodied, modality-specific, i.e. non-abstract representations. In coming to understand a particular phrase or sentence, a prior experience has to be simulated or reenacted. The representation thus activated is embodied (modality-specific) as sensorimotor regions of the brain are thereby recruited. In the paper, we will first discuss the notion of representation, clarify what it takes for a representation to be embodied or abstract respectively, and distinguish between conceptual and (other) linguistic representations. We will then put forward a characterization of cognitive control and examine its representational infrastructure. The remainder of the paper will be devoted to arguing that language augments cognitive control. To that end, we will draw on two lines of research, which investigate how language augments cognitive control: i. research on the availability of linguistic labels, and ii. research on the active usage of a linguistic code, specifically in inner speech. Eventually, we will argue that the cognition-enhancing capacity of language can be explained once we assume that it provides us with a. abstract, non-embodied representations, and with b. abstract, sparse linguistic representations that may serve as easy-to-manipulate placeholders for fully embodied or otherwise more detailed representations.